Assessment Model of Halal Good Manufacturing Practice in Bakery SMEs - Lapele, Sukmawati; Garside, Annisa Kesy; Amallynda, Ikhlasul; Lukman, Mohammad (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractBakery products are in great demand among Indonesians today. Therefore, small and medium enterprises (SMEs) of bakeries have an essential role in creating products that are guaranteed to be halal and safe, following regulations in Indonesia. This research aims to design a Halal Good Manufacturing Practice (HGMP) assessment model for “X” Bakery to improve product quality. HGMP integrates the criteria of Indonesia's Halal Assurance System, called Sistem Jaminan Produk Halal (SJPH), and Good Manufacturing Practices (GMP). The Quality Function Deployment (QFD) method evaluates company performance based on HGMP criteria and translates it into technical responses. The Pareto diagram determines the priority of HGMP criteria and technical responses. The identification results show 56 valid HGMP criteria for “X” Bakery, consisting of location and environment, buildings, facilities, employees, production, and storage. Implementing the assessment model at “X” Bakery resulted in 40 HGMP criteria that needed improvement and 12 technical responses that needed to be prioritized in meeting the HGMP criteria. This HGMP assessment model is hoped to help “X” Bakery improve the quality of halal, safe, high-quality products.Keywords: assesment model, bakery, good manufacturing practice, halal, quality function deployment AbstrakBakery merupakan salah satu produk pangan yang banyak diminati masyarakat Indonesia saat ini. Oleh karena itu, Usaha Kecil dan Menengah (UKM) bakery memiliki peran penting dalam menghasilkan produk yang terjamin kehalalan dan keamanannya sesuai dengan regulasi yang berlaku di Indonesia. Penelitian ini bertujuan untuk merancang model asesmen Halal Good Manufacturing Practice (HGMP) pada Bakery “X” dalam meningkatkan kualitas produk. HGMP mengintegrasikan kriteria Sistem Jaminan Produk Halal (SJPH) dan Good Manufacturing Practice (GMP). Metode Quality Function Deployment (QFD) digunakan untuk mengevaluasi kinerja perusahaan berdasarkan kriteria HGMP dan menerjemahkannya ke dalam respon teknis. Diagram Pareto digunakan untuk menentukan prioritas kriteria HGMP dan respon teknis. Hasil identifikasi menunjukkan 56 kriteria HGMP yang valid untuk Bakery “X” yang terdiri dari aspek lokasi dan lingkungan, bangunan, fasilitas, karyawan, produksi, dan penyimpanan. Implementasi model asesmen pada Bakery “X” menghasilkan 40 kriteria HGMP yang perlu ditingkatkan dan 12 respon teknis yang perlu diprioritaskan terlebih dahulu dalam memenuhi kriteria HGMP. Model asesmen HGMP ini diharapkan dapat membantu Bakery “X” dalam meningkatkan kualitas produk yang halal, aman, dan bermutu.Kata Kunci: assesment model, bakery, good manufacturing practice, halal, quality function deployment